The Evolution of Polish War Feature Films (1940-1980) - Shatova, Elena (International Journal of Engineering and Technology, 2018)
Introduction. The relevance of this study is explained by the rapid social and political homogenization of Europe; the â€œdisclosureâ€ of many documents indicative of sociocultural changes in Eastern Europe; an increasing chronological gap between the research subject and its researcher that enables to use scientific verification methods instead of ideologically â€œcorrectâ€ paradigms.Methods. The methodological basis of this article is the principles of systematicity and objectivity. While conducting this research, the author also used genetic, typological, comparative, hermeneutic and semiotic methods.Results. Throughout the postwar history, Polish filmmakers were bringing stories about World War II to the silver screen. The concept of a war feature film also changed depending on the postwar development of Poland.Discussion. The necessary conditions for studying the evolution of Polish war feature films based on systematicity and objectivity are as follows: the analysis of the Polish sociocultural postwar development (periodization with distinguishing essential characteristics of each period); the determination of main trends in the development of spiritual culture as a part of sociocultural processes; the analysis of the state-party politics in the sphere of culture, art and cinema.Conclusion. Throughout the postwar development, Polish filmmakers were addressing the topic of war. Their attitude to war changed depending on the countryâ€™s socio-cultural development and the evolution of its spiritual culture. For instance, war feature films were the most prominent trend in the development of the Polish cinema in the second half of the 1940s and the first half of the 1950s. Between 1956 and 1960, the Polish Film School was established and was characterized by a high interest in war-related films (alongside other topics and problems represented in the cinema of that time). In the 1970s, war feature films were still relevant but gave way to flicks about modern times. In the 1980s, this topic â€œwithdrew into the shadowsâ€ not only in cinematography but also in other artistic spheres. It was mostly used in films to better interpret other topics.Â Â